Looking closely along the shore - Serafini, Frank (Tonawanda, NY : Kids Can Press, 2008)
Up-close photographs and simple text describe the plants, animals, and objects found on a shore.
3.7
K-3
Keywords: Photography, Close-up -- Juvenile literature; Seashore biology -- Juvenile literature; Seashore -- Juvenile literature; Photography, Close-up.; Seashore biology; Seashore; Close-up photography; Coastal animals; Coastal plants; Seashore